Malignant Priapism as a Result of Metastatic Thyroid Cancer: A Hard Reality. (28th July 2021) - Vargo, Ethan; Cook, Bryson; Lane, Jason; Speakman, Eric; Parekh, Neel
Abstract : Metastasis to the penis is an extremely rare entity. Malignant priapism is defined as a persistent, nonsexual erection that is refractory to pharmacologic treatment, corporal aspiration, and surgical shunts. Furthermore, it is typically a hallmark of an advanced cancer that has metastasized, most commonly from regional organs like the prostate or bladder. We report an unusual case of malignant priapism in the setting of metastatic follicular thyroid carcinoma. To date, this is the second reported case of penile metastasis due to thyroid carcinoma and the first incidence of priapism secondary to follicular thyroid carcinoma metastasis.